ChemInform Abstract: Direct Conversion of Internal Alkynes into α‐Iodoenones: One‐Step Collaborative Iodination and Oxidation. Issue 37 (25th August 2016) - Wang, Youliang; Genoux, Alexandre; Ghorai, Subir; Chen, Hongyi; Todd, Robert; Zhang, Liming
Abstract: 2, 6‐Dichloropyridine N‐oxide as oxidant and NIS as iodination agent in stoichiometric amounts promote the title reaction regioselectively in high yields with preferred formation of Z isomers.